Global N2O Database updated - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The resulting data-set formed the basis for a modelling approach with the aim to develop a generic, data-driven, global model for N2O emissions from fertilized croplands. We are also preparing a dashboard to host data in cloud and make it public and hosting in multiple websites.